Risk, Disability, and Citizenship: U. S. Railroaders and the Federal Employers' Liability Act - Williams-Searle, John (Disability Studies Quarterly, 2008)
This paper examines how a developing work culture shaped by death and disability created a distinct federal policy approach to workplace accidents in the U. S. railroad industry. Railroaders argued that only men willing to bravely confront risks as individuals would succeed in their occupation. As railroading's dangers increased at the end of the nineteenth century, this individualistic approach was replaced by cooperative efforts to campaign for railroad safety. Railroaders, however, were still able to make claims on the government based on their relationship with danger. They argued that since their work was similar to warfare, they should be awarded federal pensions. Although this did not happen, railroaders did successfully claim a privileged citizenship status through the passage of the Federal Employers Liability Act of 1908, which recognized their argument that the dangers with which they grappled and their resulting physical sacrifices made them more than mere wage workers.